Optimizing Velocity Field Measurement with 3D-Printed Particles and MATLAB: A Cost-Effective System for Flow Visualization - José Juan Aliaga-Maraver; Ángel Antonio Rodríguez-Sevillano; María Jesús Casati-Calzada; Rafael Bardera-Mora; Estela Barroso-Barderas; Juan Carlos García-Matías; Alfonso Láinez-Muñiz; Davide Visentin (Aerospace)
This article aims to highlight the importance of including quantitative measurements when conducting flow visualization tests, such as those performed in towing tanks, within fluid mechanics analysis. It investigates the possibility of measuring velocity fields with an economically accessible technique compared to other techniques that require large financial investments, such as traditional PIV. The development of a MATLAB R2024b code based on image recognition and the use of 3D-printed tracer particles is proposed. Code workflow and how to make a correct selection of the processing parameters and its activity are explained and demonstrated on artificial images, generated by a computer, as well as real images, obtained in a 2D-test in the tank, achieving an accuracy, in absolute values, of 95%. However, the proposed velocimetry system currently has one important limitation, the impossibility of distinguishing between particles in different planes, which limits the study to two-dimensional tests. Then, the opportunity to include this technique in the study of more complex tests requires further investigation.